Tourism and social marketing - Hall, Colin Michael, 1961- (London ; New York : Routledge, 2014)
'Social Marketing is the utilisation of marketing principles and methods to encourage individual and organisational behaviour change for the public good. Traditionally the domain of government it is increasingly also utilised by non-government and non-profit organisations and other institutions of civil society as a non-regulatory means to achieve policy and public good goals. At a time when concerns over tourism's contribution to undesirable environmental, economic and social change is greater than ever, social marketing strategies are important for encouraging more appropriate and desirable behaviours by tourists and the tourism industry.Tourism and Social Marketing is the first book to comprehensively detail the relevance of social marketing principles and practice to tourism, destination management and marketing. By considering this relationship and application of social marketing approaches to key issues facing contemporary tourism development, such as the environment, this book provides significant insights into how the behaviours of visitors and businesses may be changed so as to develop more sustainable forms of tourism and improve the quality of life of destination communities. It further provides a powerful impetus to the development of tourism related forms of sustainable consumption and the promotion of ethical tourism and marketing. This innovative book is comprehensive in scope by considering a variety of relevant fields relevant to tourism and social marketing practice including, health, non - profit organisations, governance, the politics of marketing and consumption, consumer advocacy and environmental and sustainable marketing. It integrates selected international cases studies to help tourism students engage with the broader debates in social marketing, governance and the politics of behaviour change and shows the relationship of theory to practice.Written by a leading authority in the field, topical and integrative, this book will be valuable reading for students, scholars and researchers in tourism'--
'Social Marketing is the utilisation of marketing principles and methods to encourage individual and organisational behaviour change for the public good. Traditionally the domain of government it is increasingly also utilised by non-government and non-profit organisations and other institutions of civil society as a non-regulatory means to achieve policy and public good goals. At a time when concerns over tourism's contribution to undesirable environmental, economic and social change is greater than ever, social marketing strategies are important for encouraging more appropriate and desirable behaviours by tourists and the tourism industry. Tourism and Social Marketing is the first book to comprehensively detail the relevance of social marketing principles and practice to tourism, destination management and marketing. By considering this relationship and application of social marketing approaches to key issues facing contemporary tourism development, such as the environment, this book provides significant insights into how the behaviours of visitors and businesses may be changed so as to develop more sustainable forms of tourism and improve the quality of life of destination communities. It further provides a powerful impetus to the development of tourism related forms of sustainable consumption and the promotion of ethical tourism and marketing. This innovative book is comprehensive in scope by considering a variety of relevant fields relevant to tourism and social marketing practice including, health, non - profit organisations, governance, the politics of marketing and consumption, consumer advocacy and environmental and sustainable marketing'--
Includes bibliographical references (p. 244-288) and index.
Keywords: Tourism; Social marketing; BUSINESS & ECONOMICS / Consumer Behavior; TRAVEL / General